High Technological Turbulence And Company Success - Arıcı, Tuğkan; Gök, Mehmet Şahin (Burdur Mehmet Akif Ersoy University, 2023)
Customer expectations, technological changes, and high competition affect firm performance. Technological advances, along with globalization, have increased competition, which has in turn shortened product life cycles. These technological developments, combined with shortened product life cycles, have led to the emergence of technological turbulence. Technological turbulence is one of the most studied and important topics in the literature, as it brings about both success and change/instability. Therefore, many studies have examined whether technological turbulence is an advantage or disadvantage for firms. When examining the studies in the literature, it has been determined that the effects of technological turbulence on firm performance are generally analyzed. However, based on the findings obtained, clear results have not yet been established on the subject. This study focuses on SSCI indexed empirical studies published within the last five years regarding technological turbulence. The meta-analysis method was used to examine these studies. Based on the results, it has been determined that firms are more successful when operating in low technological turbulence conditions, despite taking less risk. Moreover, the study identified steps that firms can take to avoid adverse effects on their performance as the intensity of technological turbulence increases.

Müşteri beklentileri, teknolojik değişimler ve yüksek rekabet firma performansını etkilemektedir. Küreselleşmeyle birlikte yaşanan teknolojik ilerlemeler rekabeti arttırmış, artan rekabet ürün yaşam sürelerinin kısaltmış, kısalan ürün yaşam ömürleri ile teknolojik gelişmeler ise teknolojik türbülansın ortaya çıkmasına neden olmuştur. Literatürde en çok incelenen ve önemli konu başlıklarından biri olan teknolojik türbülans, beraberinde değişim ve istikrarsızlık getirdiği gibi başarıyı da getirmektedir. Bu nedenle de teknolojik türbülansın hangi durum firmalar için avantaj ya da dezavantaj unsuru olduğu pek çok çalışmada incelenmiştir. Literatürdeki çalışmalar incelendiğinde genellikle teknolojik türbülansın firma performansı üzerindeki etkilerinin incelendiği ancak elde edilen bulgulardan yola çıkarak konu hakkında henüz net sonuçlar elde edilemediği tespit edilmiştir. Bu çalışma kapsamında teknolojik türbülans odağında son 5 yılda yayınlanan SSCI endeksli ampirik çalışmalar meta analizi yöntemi ile incelenmiştir. Çalışmada ışığında firmaların düşük teknolojik türbülans koşullarında daha az risk almalarına karşın daha başarılı oldukları ve teknolojik türbülans yoğunluğu arttıkça firma performansının olumsuz etkilenmemesi için firmaların atması gereken adımlar tespit edilmiştir.
Yüksek Teknolojik Türbülans Ve Firma Başarısı
Keywords: Business Administration; İşletme